Адаптаційні підходи в навчальному процесі фахівців-електроенергетиків в умовах воєнного стану - Омеляненко, Галина Вікторівна; Черкашина, Вероніка Вікторівна; Шевченко, Сергій Юрійович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Проаналізовано умови підготовки фахівців–електроенергетиків в умовах воєнного стану в Україні. Представлено доцільність корегування відповідно умов освітнього процесу навчально-методичного комплексу дисциплін з підготовки здобувачів вищої освіти за спеціальністю 141 – "Електроенергетика, електротехніка та електромеханіка", а саме спеціалізації "Електричні системи та мережі". Запропоновано адаптаційні підходи, які підвищать рівень підготовки здобувачів вищої освіти для електроенергетичної галузі України за рахунок оптимізації навчального процесу шляхом поєднання цифрових технологій й відповідних змін в навчально-методичному комплексі дисциплін, що дозволить підвищити ефективність післявоєнного відновлювального процесу об'єктів електричних мереж та встановлення балансової надійності в об'єднаній енергетичній системі країни.

The conditions of training of electric power specialists under martial law in Ukraine are analysed. The expediency of adjusting according to the conditions of the educational process of the educational and methodological complex of disciplines for the training of students of higher education in the specialty 141 – "Electric power, electrical engineering and electromechanics", namely the specialization "Electrical systems and networks" is presented. Adaptation approaches are proposed that will increase the level of training of higher education applicants for the electric power industry of Ukraine due to the optimization of the educational process through the combination of digital technologies and relevant changes in the educational and methodological complex of disciplines, which will allow to increase the efficiency of the post-war restoration process of electrical network facilities and establish balance reliability in the unified energy system of the country.
Adaptive approaches in the education process of electrical energy specialists under the condition of marital state
Keywords: електрична система; електричні мережі; електроенергетика; навчальний процес; навчально-методичний комплекс; фахівці-електроенергетики; electrical system; electrical networks; electric power engineering; educational process; educational and methodological complex; electric power specialists